Unlocking Entrepreneurial Growth Through FinTech Credit: A Qualitative Literature Review on Digital Lending and Information Asymmetry - Agustina, Selvi; Benardi, Benardi (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2025)
This qualitative literature review explores the transformative role of FinTech credit, particularly digital lending platforms, in fostering entrepreneurial growth by addressing information asymmetry. Drawing on recent empirical and conceptual studies, the review identifies how alternative data, algorithmic credit scoring, and AI-driven risk assessments enable more inclusive and efficient credit access for underserved entrepreneurs. It highlights the potential of FinTech to reduce traditional financing barriers, especially for small and medium-sized enterprises (SMEs) with limited collateral or credit histories. However, the review also underscores risks such as algorithmic bias, data privacy concerns, and regulatory gaps. By synthesizing findings across global contexts, this study provides a nuanced understanding of how digital lending shapes entrepreneurial ecosystems. The review concludes with implications for policy, practice, and future research